Portal hypertension in pregnancy: report of a case (2014)
The coexistence of pregnancy and liver disease represents a complex clinical situation. Pregnancy develops hypervolemic state due to increased splachnic blood flow, which contributes to increased portal pressure transmitted to collateral veins that increase the risk of variceal bleeding in these patients. We report the case of a 39 years old patient in the sixth pregnancy and without any previous medical history that presented pre-sinusoidal portal hypertension, and thanks to appropriate multidisciplinary management had an uncomplicated delivery. We review the literature relevant to the case.